Conservation Agendas and the Denial of History. Reply to Penna, I. and Feller, M.C. Comments on “Laming et al. The Curse of Conservation: Empirical Evidence Demonstrating That Changes in Land-Use Legislation Drove Catastrophic Bushfires in Southeast Australia. Fire 2022, 5, 175” - Michael-Shawn Fletcher; Anthony Romano; Simon Connor; Alice Laming; S. Yoshi Maezumi; Michela Mariani; Russell Mullett; Patricia S. Gadd (Fire)
This is a reply to the comments of Penna [...]